The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/1947603520918635
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Human Platelet Lysate versus Fetal Bovine Serum for Expansion of Human Articular Cartilage–Derived Chondroprogenitors

Abstract: Purpose Articular chondroprogenitors, a suitable contender for cell-based therapy in cartilage repair, routinely employ fetal bovine serum (FBS) for expansion and differentiation. The possibility of transplant rejections or zoonoses transmissions raise a need for xeno-free alternatives. Use of human platelet lysate (hPL), a nutrient supplement abundant in growth factors, has not been reported for human chondroprogenitor expansion thus far. Our aim was to compare the biological profile of chondroprogenitors gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…14 Supplementation with platelet lysate as opposed to FBS caused chondroprogenitors to show comparatively higher alizarin red uptake. 17 Commonly reported positive MSC markers included CD105 (n = 17), CD90 (n = 20), CD73 (n = 12), while negative MSC markers included CD34 (n = 15) and CD45 (n = 15). Numerous reports evaluated the following cell surface proteins as potential markers of chondrogenesis namely CD29 (n = 12) in combination with CD49e (n = 19), CD146 (n = 4), and CD166 (n = 13).…”
Section: Table 1 (Continued)mentioning
confidence: 95%
See 1 more Smart Citation
“…14 Supplementation with platelet lysate as opposed to FBS caused chondroprogenitors to show comparatively higher alizarin red uptake. 17 Commonly reported positive MSC markers included CD105 (n = 17), CD90 (n = 20), CD73 (n = 12), while negative MSC markers included CD34 (n = 15) and CD45 (n = 15). Numerous reports evaluated the following cell surface proteins as potential markers of chondrogenesis namely CD29 (n = 12) in combination with CD49e (n = 19), CD146 (n = 4), and CD166 (n = 13).…”
Section: Table 1 (Continued)mentioning
confidence: 95%
“…14 It was also seen that for creation of xeno-free culture conditions, when human platelet lysate was used in place of FBS, progenitors displayed greater proliferation with lower expression of type I and X collagen (fibrocartilage and hypertrophy markers). 17 With regard to culture conditions producing maximum growth of progenitors, Melero et al report an optimal seeding density of 10,000 cells/cm 2 and medium volume of 0.3 mL/cm 2 . 18,19 The authors further demonstrated an efficient post-cryoviability and 17-fold expansion potential using macroporous microcarrier supplemented with 40% FCS and 1 ng/mL of TGFβ1.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…In addition, Muraglia et al also reported that addition of HPL to FBS supplement significantly enhanced the chondrocyte proliferation [42]. Kachroo et al compared the expansion of chondroprogenitor cells isolated from cartilage with HPL and FBS [43]. The authors found that chondroprogenitor cells cultured with HPL have higher proliferation but lower expression of chondrogenic (aggrecan and col II), dedifferentiation (col I) and hypertrophic markers (col X) compared to those expanded with FBS.…”
Section: Human Platelet Lysate As Replacement For Foetal Bovine Serummentioning
confidence: 99%
“…Another standard method to obtain progenitors is based on their migratory potential from cartilage explants in culture 8 , 18 . Both fibronectin adhesion assay derived 19 , 20 and migratory chondroprogenitors 8 , 21 have been likened to MSCs as delineated by the International Society for Cellular Therapy (ISCT) 2006 22 , demonstrating plastic adherence, similar surface marker expression, and trilineage differentiation potential. Extensive work on these progenitors has provided information on their growth characteristics, where fibronectin-derived cells displayed clonal growth and required additional growth factors for expansion, unlike migratory progenitors 23 .…”
Section: Introductionmentioning
confidence: 99%